A case report: Severe disseminated infection caused by Strongyloides stercoralis in an immunocompromised patient by metagenomic next-generation sequencing - Xu, Qinfu; Xi, Xiaotong; Feng, Dan; Sang, Qian; Sheng, Yanbing; Ding, Ran; Xu, Aiguo (Frontiers in Cellular and Infection Microbiology, 2023)
Background Strongyloides stercoralis (S. stercoralis) is a nematode that is widely distributed in the tropical and subtropical regions of the world and which can cause severe disseminated infection in immunocompromised individuals. However, strongyloidiasis, the disease caused by S. stercoralis, is difficult to diagnose because of its non-specific clinical presentation and the inadequate performance of conventional diagnostic methods. Case description We report the case of a 75-year-old male patient with severe disseminated infection caused by S. stercoralis. The patient had a medical history of seasonal bronchitis and, as a consequence, had taken prednisone for many years. Initial clinical tests failed to detect any pathogens, but metagenomic next-generation sequencing (mNGS) resulted in the identification of S. stercoralis in the patient’s bronchoalveolar lavage fluid (BALF) and blood. Subsequently, routine testing repeatedly detected nematode larvae in the patient’s stool and sputum. Through a combination of mNGS results and clinical symptoms, the patient was finally diagnosed with severe disseminated infection caused by S. stercoralis. Conclusion The clinical manifestations of disease caused by infection with S. stercoralis are not specific; therefore, early and accurate diagnosis is very important. mNGS can detect S. stercoralis even when it is present at only a low level. This case report supports the notion that mNGS is a valuable tool in the diagnosis of severe disseminated infections caused by S. stercoralis in immunocompromised patients.